A Public Participation GIS for Geodiversity and Geosystem Services Mapping in a Mountain Environment: A Case from Grayson County, Virginia, U.S.A. - Kyler B. Stanley; Lynn M. Resler; Lawrence W. Carstensen (Land, 2023)
Geodiversity and geosystem services are essential concepts for conservation efforts in mountain regions. Approaches that integrate both natural and human dimensions of mountain abiotic nature are best suited for this purpose; however, geodiversity research and associated conservation efforts along this vein are still developing. Here, we explore the potential of a public participation GIS, which integrates qualitative surveys with quantitative geodiversity information, to assess possible relationships between geodiversity and geosystem services for Grayson County, Virginia, U.S.A. Specifically, we: (1) used a geodiversity index to model geodiversity for the study area, (2) used a public participation GIS to map geosystem services markers, and (3) visualized geodiversity–geosystem services hotspots to uncover potential relationships between geodiversity and geosystem services values. Participants placed 318 markers, most frequently representing aesthetic (32%), artistic (22%), and educational (15%) geosystem services values. The majority (55%) of these markers corresponded to low and very low quantitative geodiversity index scores. Geosystem services value markers were clustered around population centers and protected areas. Although quantitative geodiversity measures are often used to identify and prioritize areas for conservation, our results suggest that locations valued by respondents would be missed using quantitative metrics alone. This research thus supports the need for holistic approaches incorporating place values to conserve and best understand relationships between people and abiotic aspects of mountain landscapes.